Museum of Antiquities in Osogbo: A Project of the Institute of African Studies, University of Ife - Beier, Ulli (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 1973)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Museums; Antiquities; Books; Osogbo; African Studies; Nigeria